1997
DOI: 10.1007/s003359900587
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for individual and between-family variability of the recombination rate in cattle

Abstract: We have conducted a study based on single sperm typing in a family design to assess patterns of variability of the male recombination rate in cattle. 2214 sperm of 37 bulls were typed for 11 loci on bovine Chromosomes (Chrs) 6, 23, and the sex chromosomes. Statistically significant individual variability of the recombination rate was observed for one interval in the pseudoautosomal region (PAR) of the bovine sex chromosomes; one marker interval on bovine Chr 23 exhibited individual variability that was close t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 38 publications
5
41
0
Order By: Relevance
“…Recombination rate varied twofold between extremes for the DYA-DRB3 interval and fivefold between extremes for the DRB3-PRL interval. Recently, Simianer et al (1997) reported variation in for the CYP21-D23S21 interval, which is bounded by DRB3-PRL, consistent with the findings reported herein. For the DYA-PRL interval, differences in were attributable to bull 17, for which both DYA-DRB3 and DRB3-PRL were lower (Table 2).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Recombination rate varied twofold between extremes for the DYA-DRB3 interval and fivefold between extremes for the DRB3-PRL interval. Recently, Simianer et al (1997) reported variation in for the CYP21-D23S21 interval, which is bounded by DRB3-PRL, consistent with the findings reported herein. For the DYA-PRL interval, differences in were attributable to bull 17, for which both DYA-DRB3 and DRB3-PRL were lower (Table 2).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the large number of meiotic products in a single semen sample permits accurate comparison of among different males (Park et al, 1995;Yu et al, 1996;Simianer et al, 1997) and fine-mapping of regions where variation in occurs (Hubert et al, 1994). Variation in within and between sexes may have important consequences for human and animal genetics, including accuracy of markerassisted selection and genetic diagnosis, identification of infertility and nondisjunction, and the understanding of linkage disequilibrium and haplotype evolution (Robinson, 1996).…”
Section: Introductionmentioning
confidence: 98%
“…Some of these differences are likely to be due to variation in recombination rates between individuals. This phenomenon has been demonstrated for male cattle, humans, and sheep (Yu et al 1996;Simianer et al 1997;Lien et al 1999), and it is likely that recombination rates will also vary amongst females. In addition, as shown by a recent study of human chromosome 19, sex differences in recombination rates also occur along individual chromosomes (Mohrenweiser et al 1998).…”
Section: Discussionmentioning
confidence: 83%
“…For example, while the genome-wide recombination rates in pigs are overall higher in females, its frequency in the PAR during male meiosis is almost 3-fold higher compared to female meiosis [Guo et al, 2009]. Similarly, genetic distances between the same PAR markers in cattle are 6 times longer in male meiosis than in female meiosis [Simianer et al, 1997], suggesting a higher recombination rate in this region in males.…”
Section: Recombinationmentioning
confidence: 92%